Case Study: Performance Analysis of Intersection Along Federal Route FT23 in Bandar Tangkak Using Sidra Intersection 9.1 - Ainii Amirra Asmuni; Husna Haneena S. Mohd Rafee; Izzati Syazwani Abd Halim; Mohd Erwan Sanik (Multidisciplinary Applied Research and Innovation, 2026)
The study analyzed the performance of selected intersections along Federal Route FT23 in Bandar Tangkak using SIDRA Intersection 9.1 software. The objectives were to identify peak hours along Federal Route FT23 in Bandar Tangkak, analyze the performance of selected intersections along the route, and recommend intervention to improve the performance of intersections. The volume of vehicles, including turning movements, were manually counted and collected. The result showed that severe congestion took place during peak hours (7:00 a.m. - 8:00 a.m. and 5:00 p.m. - 6:00 p.m.), with average Level of Service (LOS) ratings between E and F. The factors of this problem included poor road geometry, lack of turning lanes, and inefficient signal timing. The study recommends optimizing traffic signals, adding flyovers, and improving public transport.